2005
DOI: 10.3171/ped.2005.103.1.0050
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy in infants

Abstract: The authors conclude that ETV presents an effective alternative for the treatment of obstructive hydrocephalus in infants younger than 1 year of age. Age does not present a contraindication for ETV, nor does it increase the perioperative risk. The success of ETV is determined by the cause of the hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 19 publications
1
50
2
2
Order By: Relevance
“…Our study corroborates others in suggesting the addition of CPC does not lead to an increase in complications compared with ETV performed alone in infants, where the reported rate of meningitis is 0%-12.0%, including CSF leak in 0%-8.5%, hemorrhage in 0%-4.3%, and hygroma in 0%-4.7%. 1,10,11,13,14,17,20,34,45 However, the mortality rate of 3.5% in our series is not negligible, and, although similar to that reported by Kulkarni et al (8.3%), 29 it is higher than mortality reported in series of infants undergoing ETV/ CPC in other North American centers (0%), 44 in Uganda (1.0%), and following ETV alone worldwide, where it is closer to 0%. 1,2,10,11,13,14,20,34,45 However, comparison between cohorts of patients undergoing ETV/CPC, ETV, or CSF shunting from different studies and centers is severely lim- ited by differences in the patient populations.…”
Section: Is Etv/cpc Safe?contrasting
confidence: 54%
“…Our study corroborates others in suggesting the addition of CPC does not lead to an increase in complications compared with ETV performed alone in infants, where the reported rate of meningitis is 0%-12.0%, including CSF leak in 0%-8.5%, hemorrhage in 0%-4.3%, and hygroma in 0%-4.7%. 1,10,11,13,14,17,20,34,45 However, the mortality rate of 3.5% in our series is not negligible, and, although similar to that reported by Kulkarni et al (8.3%), 29 it is higher than mortality reported in series of infants undergoing ETV/ CPC in other North American centers (0%), 44 in Uganda (1.0%), and following ETV alone worldwide, where it is closer to 0%. 1,2,10,11,13,14,20,34,45 However, comparison between cohorts of patients undergoing ETV/CPC, ETV, or CSF shunting from different studies and centers is severely lim- ited by differences in the patient populations.…”
Section: Is Etv/cpc Safe?contrasting
confidence: 54%
“…Data from the literature suggest that the clinical response to ETV in adult patients with obstructive hydrocephalus is different from that in children, and the differences are secondary to the age at onset of hydrocephalus, CSF dynamics, and changes in brain viscoelastic properties 8,11,22) . Rates of success reported for ETV in patients 2 years old and younger vary from 0 to 83.3% with a mean of 47.8%, which is significantly lower than the success rate in older children 2,3,6,9,10,[12][13][14]16,[18][19][20][21]24,28,29) . However, when evaluating success rates of secondary ETV, Marton et al 22) reported that age does not have a statistically significant effect, which is also reflected by our data.…”
Section: Discussionmentioning
confidence: 84%
“…[4][5][6][7][8][9][10] It is considered as a better alternative to shunt surgery in obstructive HCP. Though some authors advocate ETV in patients of all ages, [1][2][3]11 others showed that patients younger than 1 year have a higher failure rate for ETVs compared with older children. 12 Therefore, we present our experience of ETV in obstructive HCP caused by congenital cerebral aqueductal stenosis (CAS), comparing between the patients below six months and above.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are pros and cons for each option, VP shunt techniques have high complication rate (20-80%). [1][2][3] Endoscopic third ventriculostomy (ETV) is well accepted for obstructive hydrocephalus of various etiologies. [4][5][6][7][8][9][10] It is considered as a better alternative to shunt surgery in obstructive HCP.…”
Section: Introductionmentioning
confidence: 99%